The Influence of Location, Product Price, and Social Media Marketing on Purchace Decision (Case Study of UPN “Veteran” East Java Fore Coffee Customers Merr Surabaya Branch) - Ananda Rizkiah Syahrani; Lia Nirawati (International Journal of Social, Economic, and Business, 2025)
Consumers make a decision to make a purchase influenced by several factors, including location, product price, and marketing strategies through social media. This study was conducted with the aim of analyzing how the influence of location, product prices, and marketing through social media on purchasing decisions of Fore Coffee Surabaya Merr Branch customers who are students of the National Development University “Veteran” East Java. This study uses a quantitative method with a survey method. Data was obtained through questionnaires distributed to 100 respondents who are active undergraduate students of the National Development University “Veteran” East Java who have purchased Fore Coffee products at the Merr Surabaya branch at least once. The data analysis technique used in this research is multiple linear regression analysis with the help of the IBM SPSS Statistics 26 application. The results showed that simultaneously, the location variable (X1), product price (X2), and social media marketing (X3) had a positive and significant effect on the purchase decision variable (Y). However, partially, the location variable (X1) does not have a significant effect on the purchase decision variable (Y). Meanwhile, the product price variable (X2) and social media marketing (X3) each have a significant positive effect on the purchase decision variable (Y). The results of these findings indicate that Fore Coffee Merr Surabaya Branch can increase consumer purchasing decisions by maintaining a competitive pricing strategy, maximizing the effectiveness of marketing through social media, and considering location factors as support.